Proceedings 2003 International Conference on Image Processing (Cat. No.03CH37429)
DOI: 10.1109/icip.2003.1246873
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of multiple sclerosis lesions from MR brain images using the principles of fuzzy-connectedness and artificial neuron networks

Abstract: Segmentation is an important step for the diagnosis of multiple sclerosis. In this paper, a method for segmentation of multiple sclerosis lesions from Magnetic Resonance (MR) brain image is proposed. The proposed method combines the strengths of two existing techniques: fuzzy connectedness and artificial neural networks. From the input MR brain image, the fuzzy connectedness algorithm is used to extract segments which are parts of Cerebrospinal Fluid (CSF), White Matter (WM) or Gray Matter (GM). Segments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Admasu et al [84] suggested an improvement to the Udupa's approach by using an ANN, instead of user, to make decision about the void pixels. This method is not dependant on the used MR modality.…”
Section: Intelligent Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Admasu et al [84] suggested an improvement to the Udupa's approach by using an ANN, instead of user, to make decision about the void pixels. This method is not dependant on the used MR modality.…”
Section: Intelligent Methodsmentioning
confidence: 98%
“…Admasu et al [84] Using fuzzy connectedness as mentioned in Udupa et al [82] and reducing false classified segments by means of ANN FN=2.7? FP=7% Boudraa et al [85] The first pass of FCM on PD-w images to discard MS/CSF and the second pass for detecting MS lesions, rejection of small lesions FN=0 SI=0.65…”
Section: Author Methods Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In medical image processing, Magnetic Resonance Imaging (MRI) plays an essential role that provides the detailed anatomical information of any part of the body. It is an important diagnostic tool for tumor, cancer, and other dangerous diseases (Fu, 1981), (Admasu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised algorithms are fully automatic and partition the regions in feature space with high density [8]. The different unsupervised algorithms are Feature-Space based Techniques, Clustering (K-means algorithm, C-means algorithm, E-means algorithm), Histogram thresholding, Image-Domain or Region Based Techniques (Split-and-merge techniques, Region growing techniques [9], Neural-network based techniques, Edge Detection Technique), Fuzzy Techniques [10], Hybrid techniques, etc. In recent years, mathematical morphology is a well-known technique used in image processing and computer vision [11] [12] [13].…”
Section: Introductionmentioning
confidence: 99%